2016
DOI: 10.1186/s40064-016-3670-7
|View full text |Cite
|
Sign up to set email alerts
|

Software project management tools in global software development: a systematic mapping study

Abstract: Global software development (GSD) which is a growing trend in the software industry is characterized by a highly distributed environment. Performing software project management (SPM) in such conditions implies the need to overcome new limitations resulting from cultural, temporal and geographic separation. The aim of this research is to discover and classify the various tools mentioned in literature that provide GSD project managers with support and to identify in what way they support group interaction. A sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 96 publications
0
18
0
1
Order By: Relevance
“…Simultaneously, there are also costs to set up the servers and online storage which are used for storing and retaining all information throughout the project [8]. Besides that, some costs may need to be invested for project management tools in order to manage the project in distributed settings [6], [34] and test tools to manage the testing activities in particular [7], [35]. The project may also need to consider the costs for other facilities such as the storage room and office space which are commonly required to store physical materials generated throughout the project [19], [36].…”
Section: β Cost Estimation Of Software Outsourcing Projectmentioning
confidence: 99%
“…Simultaneously, there are also costs to set up the servers and online storage which are used for storing and retaining all information throughout the project [8]. Besides that, some costs may need to be invested for project management tools in order to manage the project in distributed settings [6], [34] and test tools to manage the testing activities in particular [7], [35]. The project may also need to consider the costs for other facilities such as the storage room and office space which are commonly required to store physical materials generated throughout the project [19], [36].…”
Section: β Cost Estimation Of Software Outsourcing Projectmentioning
confidence: 99%
“…Recently, Chadli et al have classified GSD project management communication tools. They found that software project management in GSD lacks support of software tools for communication, coordination, and cooperation activities …”
Section: Related Workmentioning
confidence: 99%
“…They found that software project management in GSD lacks support of software tools for communication, coordination, and cooperation activities. 39 However, no study has been conducted to identify motivators for adopting social computing in GSD projects. This study is important for both practitioners and researchers to better understand the current state of the literature and practice in the context of emerging social computing technologies and their adoption motivators.…”
Section: Need For An Evidence-based Study To Identify Motivators Fomentioning
confidence: 99%
“…Therefore, the process' approach is recommended as the basis of improving the project management process, important for increasing the efficiency of the functioning of contemporary organizations [5,9,13]. [18]. The functions, which should be accomplished by information systems of particular classes, are presented in Table 1.…”
Section: Figmentioning
confidence: 99%
“…The use of specialist software may, among others, result from local conditions, specificity of the project or the area of the project which engages an organization from the branch in which the project manager is functioning. From the necessity to integrate the dedicated system with the information systems so far used in the organisation [18].…”
Section: Figmentioning
confidence: 99%